A política de saúde e a articulação entre as políticas sociais no atendimento à pessoa idosa na região de Pirituba/Perus Zona Norte do Município de São Paulo - Silva, Edlaine Faustino da (2014)
This research addresses the landmarks of Brazilian social policy, especially regarding the rights of the elderly population. It problematizes the fact that much of what is regulated by these laws has not been exercised in practice, for example, the right to home care services - as regards the health of the dependent elderly. It points out the tendency of social policy in contemporary times, the responsibility of families regarding social protection of its members, and the implications of familism for the aging worker. Taking the social policy as an object of analysis that takes place in the area where the Technical Health Supervision of Pirituba/Perus, São Paulo is located, it presents the conditions of activity for the professional worker related services, especially in the health policy and social assistance, to stress that these conditions limit the effectiveness of an articulated work. And the precariousness of services represents damage to the elderly, mainly to those that age and become dependent in the development of basic and/or instrumental activities of daily living